413 Prognostic value of the tumor infiltrating lymphocytes and the neutrophil-to-lymphocyte ratio in patients with advanced ovarian cancer. (4th December 2020) - Álvarez-Abril, Beatriz; García, Esmeralda; Morena, Pilar de la; Ivars, Alejandra; Sánchez, Manuel; Chaves, Asunción; Pastor, Francisco; Marín, Gema; Ayala, Francisco; Martinez, Elena Garcia
Abstract : Introduction/Background: Tumor infiltrating lymphocytes (TIL) and Neutrophil-to-lymphocyte ratio (NLR) have been objectified as independent prognostic factors in different tumours. There is not enough knowledge about the prognostic value of these two factors as a combination. This analysis aims to study the prognostic significance of TIL and NLR in patients with advanced ovarian cancer (OC). Methodology: Observational, single-center and retrospective analysis of a cohort of 135 patients with advanced stage OC treated between 2002 and 2019. Histological samples of ovarian tissue from the surgery of 92 patients were requested, with informed consent, and tissue microarrays (TMA) were constructed. For the TIL study, immunohistochemical staining of the TMA was made and a quantitative analysis was performed through the morphometric analysis of the lymphocytes. Samples were categorized in relation to total area as TIL 0 = absence; 1 = <25%; 2 = 25–50%; 3 = 50–75%; 4 ≥ 75%. Neutrophils and lymphocytes levels in peripheral blood at the diagnosis were collected to estimate NLR. Survival analysis was performed using Cox regression. Results: Average age 66 years (36–84 years). Median overall survival (OS): 56 months (0.92–154 m). FIGO stage: 80% III, 20% IV. Histology: 87.2% papillary serous. ECOG: 18.5% ECOG 2 at diagnosis. Surgery: primary cytoreduction/after neoadjuvant treatment: 59/59 patients. TIL and NLR study: Both variables were not correlated (Spearman's rho: -0.259, p = 0.106). 75% of patients had TILCD3 infiltration <25%. Median NLR = 3.72. The univariate analysis showed a higher OS in patients with TILCD3> 25% (HR 0.448, 95% CI 0.19 – 1.02; p = 0.057), and NLR <3.72 (p = 0.004) (figure 1 ). The combined TIL- NLR analysis stratified patients with infiltration by TILCD3 <25% into 2 subgroups with clearly different prognoses in terms of disease-free survival (DFS) (median DFS 11.49 vs 21.94 months HR 2.74 95% CI 1.18 – 6.26; p =0.019) (figure 2 ). In addition, the combined analysis in the group of patients differentiated four different prognostic subgroups for OS (p = 0.05). The multivariate analysis including PS and histology showed an independent prognostic value in the variable TIL-NLR in OS (p = 0.009) and DFS (p = 0.003). Conclusion: The combination of TILCD3 and NLR increases their prognostic value in OC. Combination prognostic factor could be very useful for improving immunotherapy strategies in advanced ovarian cancer. Disclosures: B. Álvarez-Abril: None. E. García: None. P. de la Morena: None. A. Ivars: None. M.Sánchez: None. A. Chaves: None. F. Pastor: None. G. Marín: None. F. Ayala de la Peña: None. E. García-Martínez: None.